HIV/AIDS in Russia and Eurasia - Twigg, Judyth L. (Palgrave Macmillan, 2006)
Russia and a few other Eurasian countries have been home to the fastest-growing epidemics of HIV in the world over the last several years. A study published by the U.S. National Intelligence Council in 2002 identified Russia among five "second wave" countries likely to experience explosive further increases in HIV/AIDS over the next decade if appropriate measures are not taken. It is widely acknowledged that HIV/AIDS is evolving as a serious epidemiological, social, political, and national security problem throughout the Eurasian region. Yet each of these countries confronts a unique set of challenges and strategies for facing those challenges. This volume offers country-specific accounts, authored by the leading players in the analysis of the situation and the fight against the virus